Enhancing Awareness and Implementation of a Recycling Management System for Fermented Beverage Packaging in Industrial Settings: English - Komang Widhya Sedana Putra P; Ida Bagus Putra Wiguna; Anak Agung Ngurah Dwi Narendra; Wayan Sri Maitri (Komunitas Dosen Indonesia, 2025)
ustrial waste, especially from food and beverage packaging, has emerged as a pressing environmental concern. Among the challenges is the limited awareness and understanding among students regarding appropriate recycling practices within industrial settings. This community service activity aimed to enhance students’ knowledge and awareness of recycling management systems, with a focus on fermented beverage packaging in industrial environments. Conducted by students of Universitas Pendidikan Nasional (UNDIKNAS), the program included a company visit to PT. Yakult Indonesia Persada in Mojokerto, where participants engaged in interactive counseling sessions, educational media presentations, focus group discussions, and direct observations of recycling processes. The activity resulted in high levels of student engagement, with participants actively discussing and questioning the presented material. Observational learning allowed them to grasp the practical application of the 3R principles (Reduce, Reuse, Recycle). Overall, the activity proved effective in deepening students’ environmental awareness and understanding of sustainable industrial practices while fostering stronger academia-industry collaboration.